Comparitive study of natural and commercial pectin on the growth of probiotic - Chatterjee, Emon; Manuel, Suba GA; Hasan, Syed Shamimul (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
The search for functional foods or functional food ingredients that can enhance health, is one of the leading trends in today’s food industry (Saarela et al.,2002). In this context, probiotics and prebiotics receive much attention. Functional foods or functional food ingredients exert a beneficial effect on host health and/or reduce the risk of chronic disease beyond their nutritive value. A food can be made functional by addition of a potential health promoting entity, reducing or removing concentrations of harmful components and/or modifying the nature or the bioavailability of one or more components. The first generation of functional foods was based on enrichment/ fortification with vitamins and minerals (mainly calcium). However, the concept has recently moved towards food ingredients exerting a positive effect on the gut microbiota, introducing probiotics and prebiotics (Christina 2007).